Spatial congruence and divergence between ecosystem services and biodiversity in a tropical forested landscape. (October 2018) - Alamgir, Mohammed; Turton, Stephen M.; Campbell, Mason J.; Macgregor, Colin J.; Pert, Petina L.
Highlights: We assessed multiple ecosystem services (MES) and biodiversity utilizing expert opinion. Key and high-potential MES supply is heterogeneous in a tropical forest landscape. A spatial congruence is likely to exists between certain high-potential MES and high-potential biodiversity in intact rainforest areas. A careful selection of ecosystem services is required to integrate both MES and biodiversity in tropical forests management. Abstract: Tropical forests are the storehouse of both ecosystem services and biodiversity but the interlinkages between these two components of ecosystems are yet to be fully explored. We utilized expert opinion to assess the key and multiple ecosystem services, and biodiversity in a tropical landscape. We found that key and multiple ecosystem services supply varies across the landscape and that forest disturbances reduce the capacity to supply those ecosystem services. We also found that a spatial congruence is likely to occurs between high-potential biodiversity and high-potential global climate regulation ecosystem service in the intact rainforest areas while a spatial divergence is likely to occurs in the sclerophyll and other disturbed and low tree abundance forested areas. Overall in a tropical forested landscape, a spatial congruence between high-potential multiple ecosystem services supply and high-potential biodiversity values is likely to occurs provided that the multiple ecosystem services are forest-based. Along with conserving relatively intact forests, management intervention priorities should focus on increasing tree abundance both in non-tree vegetated land cover areas and within disturbed forested areas to increase the high-potential multiple ecosystem services supply at the landscape level. A careful selection of multiple ecosystem services is required to integrate both high-potential multiple ecosystem services and high-potential biodiversity in tropical forest management.